Competition of biological agents of Streptomyces sp, Gliocladium sp, and Trichoderma harzianum to Fusarium oxysporum in Tomato Rhizophere - Penta Suryaminarsih; Tri Mujoko (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2020)
Fusarium oxysporum is a soil-borne fungus that attacks all stages of tomato plant from seedlings to mature plants. The disease occurrence on the tomato nursery can lead economically loss due to its fast and massive damage. Application of effective biological control agents is considered as promising control measure of the disease. The aim of this study was to evaluate the potential competitiveness of biological agents mixture consisting of Streptomyces sp., Gliocladium sp. and T. harzianum against F. oxysporum f. sp. lycopersici in the rhizosphere of the tomato plant. The experiment was arranged in completely randomized design with five treatment types of agents that a single biological agents Streptomyces sp. (S), a mixture of Streptomyces sp. and Gliocladium sp. (SG), a mixture of Streptomyces sp. and T. harzianum (ST), a mixture of Streptomyces sp., Gliocladium sp., and T. harzianum (SGT) and control without biological agents. Each treatment was replicated four times and consisted of 6 plants for observation purposes destructively. Descriptive analysis conducted on the pattern of colonization of the roots competition showed a growth pattern colonization of biological agents, Streptomyces sp, Gliocladium sp, T. harzianum and F. oxysporum pathogen (SGTF) was the same growth pattern of SGF and STF, where four of the microbes grew on the same side of roots as fungal pathogens, in all parts of the root sprouts. Given biological agent Streptomyces sp, Gliocladium sp., dan Trichoderma harzianum decreased fusarium wilt diseases severity of tomato. Weight root of tomato plants was applied by biological agents was 9.2 g greater than plant without biological agents, which were 2.5 g. The observation on tomato indicated root colonization occurs, especially on the base of the stem-roots by a mixture of biological agents T. harzianum and Gliocladium sp.